Immigrants’ crises and challenges portrayed in The Lonely Londoners, Home Fire and White Teeth - Binte Monir, Fatimah (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Master of Arts in Teaching to Speakers of Other Languages, 2020.